Recurrent Phaeohyphomycosis due to Phaeoacremonium alvesii Identified with Internal Transcribed Spacer and Beta-tubulin Gene Sequencing - Ryoko Kimura; Nanako Yamada; Yuichi Yoshida; Ayako Ito; Takashi Horie; Kazushi Anzawa; Takashi Mochizuki; Osamu Yamamoto (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)